Theoretical model of a fluidized bed solar reactor design with the aid of MCRT method and synthesis gas production. (April 2020) - Gomaa, Mohamed R.; Al-Dmour, Nesrien; AL-Rawashdeh, Hani A.; Shalby, Mohammad
Abstract: Energy is one of the most critical inputs for the development and economic growth. The objective of this study is to investigate the possibilities of fulfilling such global market demands, even going so far as to provide for a more reliable power source that can extend its reach to rural and remote areas. Therefore, in this work, investigating the gasification of carbonaceous materials (biomass materials) was conducted to produce syngas in a theoretically modelled solar reactor (fluidized bed) design. The Monte Carlo ray tracing method was utilized to design an indirectly irradiated fluidized bed solar reactor. This solar reactor was used in the co-gasification process of 50% olive-pomace and 50% lignite mixture to investigate the performance of gasification with changing the H2 O: fuel and O2 : fuel ratios. Such a solar reactor model approves the ability to use solar energy as the primary heat source in gasification. Oxygen could be fed into a solar gasification reactor reliably to increase temperatures by combusting some of the used feedstock during the frequency of solar transients. The development of the stoichiometric equilibrium model for the co-gasification process was aimed to investigate the solar reactor performance where the addition of lignite to olive-pomace played a significant role in reducing tar formation and increasing the gasification temperature. Monte Carlo ray tracing method presented the absorbed fluxes over a 40 × 40 mm area centre of the tube where the peak flux and average heat flux were 592.4 and 162.5 kW/m 2, respectively. Also, the results indicated that, the optimum H2 O: fuel and O2 : fuel ratios were 1.16 and 0.33, respectively. The change of H2 O: fuel ratio has less effect than the change of O2 : fuel ratio in the co-gasification process. Highlights: This study provides for innovative renewable technologies. Modeling of indirectly irradiated solar reactor utilizing MC ray tracing method. Study of co-gasification process between coal and biomass using a TDEM. Three modes of the receiver operation via adjusting the O2 levels during the process. Olive pomace content incorporation should not exceed 50% (w/w) to guarantee gasification stabilization.